POLITYKA PIASTÓW ŚLĄSKICH I WIELKOPO LSKICH WOBEC TEMPLARIUSZY NAD ŚRODKOWĄ ODRĄ I DOLNĄ WARTĄ W XIII WIEKU - Przybył, Maciej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
This article revolves around patrimonies for the Templars on the borders of Lubusz, Wielkopolska and Pomerania regions. The author presents the course of these patrimonies in a context of the political actions on the part of Piast dukes in Silesia and Wielkopolska. The article consists of three parts: the first of them presents the invitation of the Templars to Poland, with the (nearly concurrent) contribution made in the third decade of the 13th century by Henry I Bearded and Władysław Odonic. Part two is dedicated to the controversial patrimony of Chwarszczany on the Myśla, the biggest Templars’ commandery on the central Oder and the lower Warta and Wielka Wieś – a dominion located on the Lubusz and Wielkopolska border. In the last part, attention has been drawn to the subsequent patrimonies for the Templars in the area in question from 1234-1261.